If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 16) = 6x Reorder the terms: 2(16 + x) = 6x (16 * 2 + x * 2) = 6x (32 + 2x) = 6x Solving 32 + 2x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 32 + 2x + -6x = 6x + -6x Combine like terms: 2x + -6x = -4x 32 + -4x = 6x + -6x Combine like terms: 6x + -6x = 0 32 + -4x = 0 Add '-32' to each side of the equation. 32 + -32 + -4x = 0 + -32 Combine like terms: 32 + -32 = 0 0 + -4x = 0 + -32 -4x = 0 + -32 Combine like terms: 0 + -32 = -32 -4x = -32 Divide each side by '-4'. x = 8 Simplifying x = 8
| 9=-a+13 | | -7(3b+3)+22b-8=0 | | 2x^3-6x^2-8x=0 | | -4b+-3=1 | | (d-5)(3d-2)=0 | | 3x+29=8x+4 | | 5a+5=35 | | 3c=-3 | | 0.5x+5=51 | | B-3=-5 | | 6(x+35)=11x | | 8=a+3 | | 8x-15=3x | | X^2=3X+18 | | D=-16T^2-4T+472 | | 5x-5=4x | | x^2-2x^3+x=0 | | 2x-4=3x-7 | | 345-67g=578-467*45 | | 9-3(y+4)=18 | | 2x+5=79 | | 5x-5=-20 | | n=16-3*0.4+2+2 | | 8x-4=24 | | 9(x+10)+5=113 | | 10=y-22 | | 8-4x-28=4 | | N-12=54-n | | N-1212=54-n | | X^2+8x+25=0 | | S=187.22S | | 28=11x-5 |